Different light color temperatures in the morning on the effectiveness of rehabilitation training in patients with ischemic stroke: a prospective, single-center, randomized controlled clinical trial - Nan Wang; Yan Xue; Tongyue Wang; Fengxi Qiu; Cheng Li; Zhiyuan Wang; Jianke Jiang; Yi Lu; Yingqi Shao; Zhongfei Bai; Danmei Lan; Qilong Hu; et al. (Journal of NeuroEngineering and Rehabilitation)
Abstract Background Stroke is a leading cause of death and disability worldwide, especially in China, where its incidence is rising. Post-stroke rehabilitation is crucial for restoring neurological function and improving quality of life. Light therapy, a non-pharmacological intervention, is gaining attention for its potential to promote neuroplasticity and enhance brain circulation. Warm and cold light, characterized by different color temperatures, have demonstrated beneficial effects on sleep quality, neurological recovery, and emotional well-being in stroke patients. However, the underlying mechanisms remain incompletely understood. This study explores the effects of different light color temperatures on stroke recovery to optimize rehabilitation approaches. Methods The study was designed as a prospective, single-center, randomized controlled trial. 48 patients with ischemic stroke were randomly divided into three groups (1:1:1): warm light group (WLG, 500 lx, 3000 K, n = 16), cold light group (CLG, 500 lx, 6500 K, n = 16), and control group (CG, 500 lx, 5000 K, n = 16). Patients in all three groups received 60 min of rehabilitation therapy daily, from Monday to Friday between 8:30 and 9:30 AM, under light environments with different color temperatures. National Institutes of Health Stroke Scale (NIHSS), Short Form-36 (SF-36), Self-Rating Sleep Scale (SRSS), and levels of interleukin 6 (IL-6), norepinephrine (NE) and melatonin (MT) were measured before and after 4 weeks of intervention. Results After 4 weeks intervention, CLG showed a significant reduction of NIHSS when compared to CG(p < 0.001, partial η2 = 0.316) and WLG(p = 0.003, partial η2 = 0.237). Although all three groups showed significant reductions in SRSS scores in the within-group comparisons, between-group comparisons revealed that CLG demonstrated a significantly greater reduction in SRSS compared to CG (p = 0.004, partial η2 = 0.253) and WLG (p = 0.007, partial η2 = 0.241). Regarding the SF-36, the physical component summary (PCS) score significantly decreased in both CG (Δ = –5.34 ± 7.35, p = 0.011) and WLG (Δ = –3.63 ± 4.68, p = 0.015), while CLG showed a significant improvement (Δ = 4.28 (8.78), p = 0.024). Between-group analysis demonstrated that post-intervention PCS scores were significantly higher in CLG compared to CG (p = 0.001, partial η2 = 0.323) and WLG (p = 0.002, partial η2 = 0.326), with no significant difference between CG and WLG (p = 0.104). Mental component summary (MCS) scores showed no statistically significant differences either within or between groups. No significant changes in NE and IL-6 levels were observed across all groups. CLG showed a significant reduction of MT when compared to WLG(p = 0.018, partial η2 = 0.174). No apparent adverse events were reported. Conclusions This study demonstrated that cold light therapy significantly improves neurological function, sleep quality, physical health status, including better performance on the physical component of quality of life in post-stroke patients, while warm light shows moderate benefits in sleep. These results support the integration of light-based interventions as adjunctive strategies in post-stroke care. Trial registration The study was registered in Chinese Clinical Trial Registry as a clinical trial ID (ChiCTR2200057541), March 14, 2022.